Pengaruh Likuiditas, Leverage, Aktivitas, Ukuran Perusahaan, dan Sales Growth Terhadap Profitabilitas - Fara Zumrotul Mufalichah; Ida Nurhayati (Universitas Pendidikan Ganesha, 2022)
Abstract This study aims to examine the effect of liquidity, leverage, activity, company size and sales growth on the profitability of manufacturing companies listed on the IDX for the period (2018-2020). The research population includes all manufacturing companies listed on the IDX for the period (2018-2020). The sampling technique used was purposive sampling. The data obtained were 335 samples. The data analysis method used is multiple linear regression analysis. The results of this study indicate that liquidity and sales growth have a significant positive effect on profitability, while leverage, activity, and firm size have no effect on profitability. Keywords: Profitability, Liquidity, Activity, Sales Growth